1977
DOI: 10.1063/1.433724
|View full text |Cite
|
Sign up to set email alerts
|

Matrix isolation spectroscopic study of the free radical HCCN

Abstract: The free radical HCCN was produced in an Ar matrix via photolysis of its precursor diazoacetonitrile, NNCHCN, with radiation of wavelengths longer than 350 nm. The ir spectra of HCCN and three isotopic modifications (DCCN, HC13CN, and HCC15N) were obtained, and normal coordinate analyses based on two different geometries, bent and linear, were carried out. The results provide a determination of the general valence force field, and favor the linear, allenic configuration H–Ċ=C=Ṅ. The electronic spectrum of HCCN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 28 publications
3
41
0
Order By: Relevance
“…A hot band involving the upper state 1 ϩ 5 , specifically 1 ϩ 5 -5 , had been observed previously (13) with its origin at 3226.597 cm Ϫ1 . Earlier estimations of the energy of the 5 Ϫ1 found a number of lines with a time profile typical of the radical HCCN as shown in Fig. 1a and 1b.…”
Section: Observations and Analysismentioning
confidence: 94%
See 3 more Smart Citations
“…A hot band involving the upper state 1 ϩ 5 , specifically 1 ϩ 5 -5 , had been observed previously (13) with its origin at 3226.597 cm Ϫ1 . Earlier estimations of the energy of the 5 Ϫ1 found a number of lines with a time profile typical of the radical HCCN as shown in Fig. 1a and 1b.…”
Section: Observations and Analysismentioning
confidence: 94%
“…The primary interest was on whether this molecule is linear or bent; thus, most investigations have focused on the HCC bending potential. Early experimental studies based on matrix isolation EPR (1-4) and infrared spectra (5) indicated that HCCN is a linear triplet molecule in its ground electronic state. This was supported by analysis of the millimeter spectrum of HCCN in the gas phase reported by Saito et al (6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early experiments by Dendramis and Leroi using matrix infrared (IR) and ultraviolet (UV) spectroscopy concluded the radical to be linear by performing a normal mode analysis 16 . Additionally, Saito et.…”
Section: Introductionmentioning
confidence: 99%